Optimalisasi Limbah Kerang Menjadi Cermin Hias Estetis untuk Mendorong Kemandirian Ekonomi Masyarakat Talang Kelapa Palembang - Yusro Hakimah; Zahwa Aulia Hasana; Putri Resa Diah Pertiwi (LKP KARYA PRIMA KURSUS, 2026)
This community service activity aims to enhance community economic independence through the optimization of shell waste into decorative mirror products with aesthetic and economic value. The method applied a participatory approach consisting of problem identification, hands-on training, production and marketing assistance, and evaluation. The results indicate a significant improvement in participants’ knowledge, skills, and entrepreneurial understanding. Before the program, most participants were categorized as having low skills and marketing knowledge; however, after the intervention, the majority were able to independently produce decorative mirrors. Furthermore, the level of participant satisfaction was very high, indicating that the applied training method was effective and aligned with community needs. The program also contributed to increased motivation among participants to start waste-based businesses and shifted their perception of waste into a valuable economic resource. Despite these achievements, limitations remain, particularly in terms of production scale and market access. Therefore, further efforts are needed to expand the impact through stronger networking and digital marketing strategies to ensure sustainability.